2016
DOI: 10.1021/acs.est.5b04466
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Production at a Fully Covered Wastewater Treatment Plant: Results of a Long-Term Online Monitoring Campaign

Abstract: The nitrous oxide emissions of the Viikinmäki wastewater treatment plant were measured in a 12 month online monitoring campaign. The measurements, which were conducted with a continuous gas analyzer, covered all of the unit operations of the advanced wastewater-treatment process. The relation between the nitrous oxide emissions and certain process parameters, such as the wastewater temperature, influent biological oxygen demand, and ammonium nitrogen load, was investigated by applying online data obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 38 publications
(83 reference statements)
4
55
1
Order By: Relevance
“…0, electricity accounts for 35% of the total impact and the total plant greenhouse gas (GHG) emissions for 56%. According to our measurements, the N 2 O emissions comprised 80% of the total emissions, which is in line with the results reported by Kosonen et al (2016). Remaining impacts are characterized as follow: composting (4.5%), effluent release (2.3%), transport (1.5%) and production of chemicals used (1.3%).…”
Section: Global Warming Potentialsupporting
confidence: 90%
See 1 more Smart Citation
“…0, electricity accounts for 35% of the total impact and the total plant greenhouse gas (GHG) emissions for 56%. According to our measurements, the N 2 O emissions comprised 80% of the total emissions, which is in line with the results reported by Kosonen et al (2016). Remaining impacts are characterized as follow: composting (4.5%), effluent release (2.3%), transport (1.5%) and production of chemicals used (1.3%).…”
Section: Global Warming Potentialsupporting
confidence: 90%
“…for influent N (Kosonen et al 2016). In the scSBR of the SCENA system, the N 2 O emissions were 1.42% of the N influent load of the side-stream line, which is in accordance with the range of 0.24-1.49% previously measured by Frison et al (2015).…”
Section: Inventory Analysismentioning
confidence: 99%
“…A 12-month online monitoring of N2O production at a fully covered WWTP had showed an annual N2O emissions of 168 g/PE/year and an emission factor of 1.9% of the influent nitrogen (N) load, which was in good agreement with other full-scale WWTPs with long-term online monitoring (Kosonen et al, 2016).…”
Section: Ghg Emissions From Wwtpssupporting
confidence: 65%
“…In the current study, N 2 O gas from wastewater treatment using the activated sludge process was monitored for one year. Kosonen et al reported annual N 2 O emissions of 168 g/PE/year and 0.019 g N 2 O-N/g N load from a fully covered underground wastewater treatment plant [5]. Daelman et al reported N 2 O emissions of 0.028 g N 2 O-N/g N load from a full-scale municipal wastewater treatment plant [3].…”
Section: Introductionmentioning
confidence: 99%